2019
DOI: 10.1177/0886260519881004
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence: Barriers to Action and Opportunities for Intervention Among Health Care Providers in São Paulo, Brazil

Abstract: Health care providers (HCPs) who directly interact with women play a critical role in intimate partner violence (IPV) prevention and response. The aim of this study was to identify the structural and interpersonal barriers to IPV response among HCPs working in public health clinics in Santo André, Brazil. Eligible participants included all HCPs providing direct care to individuals at three public health clinics. Participants self-administered an adapted Knowledge, Attitudes, and Practices survey on IPV. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…A possible explanation for this occurrence could be a conversion of factors such as the sum of different participants who had experienced different types of violence, cultural issues of submission of the feminine to the masculine, (3) and given the research site that were a Basic Health Unit that is part of Brazilian Public Health System. (10) The highest prevalent type of violence was psychological, which confirmed the initial hypothesis of this study. This type of violence was followed by physical and sexual, which are similar results of those reported in the literature.…”
Section: ❚ Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A possible explanation for this occurrence could be a conversion of factors such as the sum of different participants who had experienced different types of violence, cultural issues of submission of the feminine to the masculine, (3) and given the research site that were a Basic Health Unit that is part of Brazilian Public Health System. (10) The highest prevalent type of violence was psychological, which confirmed the initial hypothesis of this study. This type of violence was followed by physical and sexual, which are similar results of those reported in the literature.…”
Section: ❚ Discussionsupporting
confidence: 86%
“…Primary Health Care (PHC), the front door of the Brazilian Public Health System, provides the first care for violence victims, in addition, PHC is responsible to provide the necessary treatments for them to recover from the violence suffered. (10)…”
Section: ❚ Introductionmentioning
confidence: 99%
“…This analysis was part of a larger study examining individual experiences and community perceptions of GBV. Detailed information on the methods of the parent study are available in earlier publications [20,21]. The project was conducted in partnership with the SPM in Santo André, the Municipal Ministry of Health, and the ABC School of Medicine (Faculdade de Medicina do ABC).…”
Section: Methodsmentioning
confidence: 99%
“…Future research should seek to better understand the impact of disparity conditions on social comorbidities, particularly potential interventions that address these conditions. In the context of Brazil, violencespecific policies such as the Maria da Penha law have seen some limited success; however, the integration of these conceptual frameworks may lead one to examine broaderreaching policies that address social determinants that are linked to social comorbidities such as poverty and genderbased inequity [2,20,21].…”
Section: Broadening An Understanding Of Disparity Conditionsmentioning
confidence: 99%
“…Seven HBW are currently in operation including our study site in Curitiba, Brazil (Curitiba, 2016). Despite the promise of these structures, impunity for perpetrators of violence (Evans et al, 2018), lack of trust in the health and legal sectors (Evans et al, 2020a(Evans et al, , 2020b, barriers to addressing IPV among health providers (Evans et al, 2019), and other factors impede the prevention of IPV and femicide. A recent study revealed that the Curitiba's Metropolitan area faces higher rates of femicide compared to the state average and the most common location of these crimes was in the home (35%) using firearms (44%) (Wanzinack et al, 2020).…”
Section: Introductionmentioning
confidence: 99%